Review of the almanac: Balyuk N.A., Vychugzhanin A.L. (еds.) Tobolsk and all Siberia: historical, cultural, literary and artistic almanac: in 2 books. Tyumen – the capital of villages. Tobolsk: Izdatel’skii otdel TROBF «Vozrozhdenie Tobol’ska», 2023. Book 1. 480 p.; Book 2. 536 p. - V. V. Kondrashin (Вестник Самарского университета: История, педагогика, филология)
The article presents a review of the historical and cultural literary and artistic almanac «Tyumen – the capital of villages». This publication is relevant and socially significant in the context of modern problems of the Russian village and the agricultural sector of economy as a whole. In the almanac, the history of Russian village is shown at the regional level of the former Tobolsk province (now Tyumen region) and the micro level of selected villages of this region using an interdisciplinary approach by the authors’ collective. The authors are professional historians, ethnographers, and local historians. The almanac is one of the successful examples of understanding the history of peasantry of Russia at the regional level.